La "paraipotassi" con ma in italiano antico: verso una tipologia sintattica della correlazione - Mazzoleni, Marco (Verbum – Analecta Neolatina, 2002)
"Parahypotaxis" is the name traditionally assigned to Old Italian sequences of dependent clauses with following main clauses introduced by e ("and") or sì ("thus"). Sì is not a coordinating conjunction like e but an adverbial element, and for this reason the relevant examples should be taken away from the category; instead I would suggest also taking into account parahypotactic structures with main clauses introduced by the adversative coordinating conjunction ma ("but"), a kind of combination which in my opinion was underestimated in the traditional literature.